Rare full-body imprint of the giant Asiocoleidae (Coleoptera: Archostemata) from the Lower Triassic sheds light on the morphology of the family - Arakelyan, Stepan A.; Strelnikova, Olesya D.; Felker, Anastasia S.; Yan, Evgeny V. (Zootaxa, 2025)
Anakitium storozhenkoi Arakelyan & Yan, gen. et sp. nov. of the family Asiocoleidae (Coleoptera: Archostemata) was discovered in the Tunguska coal basin at the Anakit-3 locality (Lower Triassic; Krasnoyarsk Krai, Russia). The holotype shows a well-preserved full-body imprint with partially visible dorsal and nearly complete ventral aspects. Previous well-preserved complete specimens of this family are known only from the Jurassic. The general body structure of Anakitium storozhenkoi is in many ways similar to later Archostemata, including recent Cupedidae and Ommatidae, while the elytral structure exhibits several unique and likely ancestral characters. Discovery of Anakitium provides new insights into the morphology of Asiocoleidae, which was previously known mainly from isolated elytra. The taxonomic placement of A. storozhenkoi and certain genera within Asiocoleidae is discussed.